Prediction of honey adulteration using machine learning-assisted OIRD - Shanzhe Zhang; Shunyi Li; Hao Yang; Enhao Tang; Xiaorong Sun; Yuan Gao; Cuiling Liu; Kun Zhao (Food Bioscience, 2026)

Multiscale characterization of the adsorption behavior at oil-water interface of β-cyclodextrin - Xiaorong Sun; Liyi Chen; Haoyue Zhang; Chonghao Bi; Cuiling Liu; Aoxue Qie; Kun Zhao; Shanzhe Zhang; Xuecong Liu (Journal of Food Engineering, 2026)

Climate-driven dynamics of surface water temperature and its coupled responses to lake heatwaves and cyanobacterial blooms in Lake Taihu - Lei Sun; Ruiting Xu; Yakun Feng; Haozhang Dai; Menglin Yuan; Chenhui Wu; Hao Wang; Ya Liu; Cuiling Jiang (Journal of Environmental Management, 2026)

Chiral Ratiometric Fluorescent Silicon Nanoparticles for “Turn-on” Enantioselective Recognition of Tryptophan - Chen Liu; Yaning Duan; Cancan Lu; Yu Fu; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2026)

Genome-wide analysis of Zoysia japonica REVEILLE family identifies ZjRVE8-1 as a positive cold-tolerance regulator - Cuiling Liu; Liangliang He; Ming Jiang; Zhihao Wu; Jieyi Li; Chao Liu; Quanrui Su; Jingyi Sun; Fei Xu; Shu Chen (Plant Cell Reports, 2026)

Nationwide occurrence of emerging benzophenone, benzotriazole, salicylate and triazine ultraviolet filters in coastal sediment of China: Spatial distribution, source and ecological risk - Zhao Tang; Zilan Wu; Xuan Jia; Xing Liu; Xiaodan Pei; Zehua Liu; Xingan Xiong; Jianzhong Li; Xi Liu; Cuiling Wu; Ziwei Yao (Environmental Research, 2025)

Different AOM processes driving the formation of carbonate crusts and nodules in the Okinawa Trough - Yucheng Zhou; Hong Cao; Zhilei Sun; Wei Geng; Chenhui Liu; Xilin Zhang; Cuiling Xu; Taiheng Lv; Shixing Li; Ye Chen; Xuejun Jiang; Dong Zhang; et al. (Marine and Petroleum Geology, 2025)

New silicon nanoparticles for “turn-on” detection of salicylaldehyde in food based on ESIPT mechanism - Jialu Zhang; Yu Fu; Peng Chen; Bowen Liu; Cuiling Ren (Food Chemistry, 2025)

The chemosensory protein CSP4 increased dinotefuran tolerance in Diaphorina citri adults - Cuiting Liu; Yaoyao Chen; Xinyi Xie; Huiyin Hu; Junxian Wu; Cuiling Ye; Rui Tang; Zhongzhen Wu; Benshui Shu (Pesticide Biochemistry and Physiology, 2025)

Combined transcriptome and metabolome analyses provide insights into host adaptation mechanism of Spodoptera frugiperda to cruciferous vegetables - Benshui Shu; Yuning Li; Cuiting Liu; Junying Wu; Cuiling Ye; Jintian Lin; Jingjing Zhang (Journal of Insect Physiology, 2025)

Inhalation risk assessment on 14 organic chemicals in children's masks based on the Monte Carlo stochastic modeling method - Yunbo Wang; Guixiao Li; Lihua Yu; Xiangke He; Xiaofeng Wei; Zhongxian Liu; Guiqin Zhang; Cuiling Gao (Atmospheric Pollution Research, 2025)

A machine learning approach fusing multisource spectral data for prediction of floral origins and taste components of Apis cerana honey - Zhaolong Liu; Hongxia Li; Nan Liu; Cuiling Liu; Xiaorong Sun; Lanzhen Chen (Food Research International, 2025)

Integrating AI with detection methods, IoT, and blockchain to achieve food authenticity and traceability from farm-to-table - Zhaolong Liu; Xinlei Yu; Nan Liu; Cuiling Liu; Ao Jiang; Lanzhen Chen (Trends in Food Science & Technology, 2025)

Rapid and nondestructive identification of rice storage year using hyperspectral technology - Xiaorong Sun; Xinpeng Zhou; Cuiling Liu; Chunlin Li; Shanzhe Zhang; Dongyu Zheng (Food Control, 2025)

ChatGPT-based meta-analysis for evaluating the temporal and spatial characteristics of deoxynivalenol contamination in Chinese wheat - Chuanzhi Jiang; Sen Li; Di Cai; Jin Ye; Qinghang Bao; Cuiling Liu; Songxue Wang (Journal of Hazardous Materials, 2024)

Response mechanisms of submerged macrophytes and epiphytic biofilms to single and coexisting per-and poly-fluoroalkyl substances and antibiotics stress - Yakun Feng; Cuiling Jiang; Wei Zhang; Lei Sun; Zequn Fan; Can Lu; Lei Jiang; Ruiting Xu; Ya Liu (Journal of Environmental Chemical Engineering, 2024)

Quantifying microplastics in sediments of Jinzhou Bay, China: Characterization and ecological risk with a focus on small sizes - Xue Yu; Yufei Liu; Cuiling Tan; Lifang Zhai; Tianjiao Wang; Jing Fang; Bo Zhang; Weiqi Ma; Xueqiang Lu (Science of The Total Environment, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Flexible human-machine interface touch system based on double-network solid-state ionic conductive elastomers - Wang Zhan; Qi Zhang; Zhilu Ye; Yuhao Wang; Zihao Yang; Yijing Wang; Cuiling Zhang; Zeying Zhang; Li Xue; Feng Ma; Zhiguang Wang; Niancai Peng; et al. (Chemical Engineering Journal, 2024)

Using organic fertilizer to mitigate organic-inorganic fouling in agricultural saline wastewater irrigation systems - Tahir Muhammad; Cuiling Jiang; Zeyuan Liu; Irum Manan; Yang Xiao; Yunkai Li (Chemosphere, 2024)

A new approach to extract the upright maize straw from Sentinel-2 satellite imagery using new straw indices - Jingping Zhou; Xiaohe Gu; Cuiling Liu; Wenbiao Wu; Yuchun Pan; Qian Sun; Sen Zhang; Xuzhou Qu (Computers and Electronics in Agriculture, 2024)

Red Emission Carbon Nanoparticles Which Can Simultaneously Responding to Hypochlorite and pH - Yinghua Liu; Wenxiu Duan; Huiqing Li; Jiang Wu; Dan Liu; Jiaying Mi; Shengda Qi; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2023)

The changing characteristics of propagation time from meteorological drought to hydrological drought in the Yangtze River basin, China - Xiaoyu Zhang; Dunxian She; Jun Xia; Liping Zhang; Cuiling Deng; Zheqiong Liu (Atmospheric Research, 2023)

NAC1 regulates root ground tissue maturation by coordinating with the SCR/SHR–CYCD6;1 module in Arabidopsis - Chuantian Xie; Cuiling Li; Fengxia Wang; Feng Zhang; Jiajia Liu; Junxia Wang; Xiansheng Zhang; Xiangpei Kong; Zhaojun Ding (Molecular Plant, 2023)

Stable isotope and elemental profiles determine geographical origin of saffron from China and Iran - Jing Nie; Jian Yang; Cuiling Liu; Chunlin Li; Shengzhi Shao; Chunxia Yao; Bilian Chen; Yi Tao; Fang Wang; Yongzhi Zhang; Karyne M. Rogers; Ping Wang; et al. (Food Chemistry, 2023)

Recent advances in Chinese food authentication and origin verification using isotope ratio mass spectrometry - Chunlin Li; Xuming Kang; Jing Nie; An Li; Mohamed A. Farag; Cuiling Liu; Karyne M. Rogers; Jianbo Xiao; Yuwei Yuan (Food Chemistry, 2023)

Discovery of potential anti-SARS-CoV-2 drugs based on large-scale screening in vitro and effect evaluation in vivo - Haoran Peng; Cuiling Ding; Liangliang Jiang; Wanda Tang; Yan Liu; Lanjuan Zhao; Zhigang Yi; Hao Ren; Chong Li; Yanhua He; Xu Zheng; Hailin Tang; et al. (Science China Life Sciences, 2022)

Identification of WRKY transcription factors responding to abiotic stresses in Brassica napus L. - Hao Chen; Yongfeng Wang; Jiong Liu; Tian Zhao; Cuiling Yang; Qunying Ding; Yanfeng Zhang; Jianxin Mu; DaoJie Wang (Planta, 2022)

First report of brassica yellows virus infecting cowpea in China - Shunyu Xiang; Cuiling Tian; Changyun Liu; Haoran Peng; Jing Wang; Sihan Ye; Daibin Wang; Chen Xu; Xianchao Sun; Yang Xue (Journal of Plant Pathology, 2021)

The biosynthesis of camptothecin derivatives by Camptotheca acuminata seedlings - Yanni Sun; Ning Zhang; Cuiling Wang; Xiao Bai; Yahui Wei; Jianli Liu (Natural Product Research, 2021)

Distribution of camptothecin biosynthetic intermediates and identification the rate-limiting step of camptothecin biosynthesis - Yanni Sun; Ning Zhang; Cuiling Wang; Yahui Wei; Jianli Liu (Natural Product Research, 2021)

Ochratoxin A induces nephrotoxicity in vitro and in vivo via pyroptosis - Hu Li; Xinru Mao; Kai Liu; Jiahao Sun; Benrui Li; Rahmani Mohammad Malyar; Dandan Liu; Cuiling Pan; Fang Gan; Yunhuan Liu; Kehe Huang; Xingxiang Chen (Archives of Toxicology, 2021)

HMGB1: an important regulator of myeloid differentiation and acute myeloid leukemia as well as a promising therapeutic target - Lulu Liu; Jingjing Zhang; Xianning Zhang; Panpan Cheng; Lei Liu; Qian Huang; Haihui Liu; Saisai Ren; Peng Wei; Cuiling Wang; Cuiyun Dou; Lulu Chen; et al. (Journal of Molecular Medicine, 2021)
High mobility group box 1 (HMGB1) is a non-histone nuclear protein which has been intensively studied in various physiological and pathological processes including leukemia. Here in this study, we further demonstrated that HMGB1 presents higher expression in the bone marrow mononuclear cells of acute myeloid leukemia (AML) patients compared with the normal controls and contributes to the AML pathogenesis and progression by inhibiting apoptosis, facilitating proliferation, and inducing myeloid differentiation blockade of AML cells. Mechanistic investigation revealed that transforming growth factor beta-induced (TGFBI) acts as a potential downstream target of HMGB1 and lentivirus-mediated knockdown of TGFBI expression impaired phorbol-12-myristate-13-acetate (PMA) and all-trans retinoic acid (ATRA)–induced myeloid differentiation of AML cell lines. On the other hand, chidamide, an orally histone deacetylase inhibitor, decreases HMGB1 expression significantly in AML cells with concomitant upregulation of TGFBI expression, and confers therapeutic effect on AML by inducing cell differentiation, apoptosis and inhibiting cell proliferation. In conclusion, our findings provide additional insights that HMGB1 is a promising therapeutic target of AML, and also present experimental evidence for the clinical application of chidamide as a novel agent in AML therapy by downregulating HMGB1 expression. Key messages HMGB1 induces cell proliferation and myeloid differentiation blockade and inhibits apoptosis of AML cells. TGFBI acts as a potential target of HMGB1. Chidamide, a selective HDAC inhibitor, confers promising therapeutic effect for AML via downregulating HMGB1 expression.

A new phenolic glycoside from Trollius chinensis Bunge with anti-inflammatory and antibacterial activities - Jie Feng; Danyang Zhao; Qiannan Xu; Xiangzhong Liu; Mi Zhou; Xiansheng Ye; Ting Lin; Guanghui Wang; Cuiling Sun; Rong Ding; Wenjing Tian; Haifeng Chen (Natural Product Research, 2020)

Decylubiquinone suppresses breast cancer growth and metastasis by inhibiting angiogenesis via the ROS/p53/ BAI1 signaling pathway - Jinghua Cao; Xiaohua Liu; Yang Yang; Bo Wei; Qianming Li; Guanquan Mao; Yajun He; Yuanyuan Li; Lingyun Zheng; Qianqian Zhang; Jiangchao Li; Lijing Wang; et al. (Angiogenesis, 2020)

Population distribution patterns and changes in China 1953–2010 - Cuiling Liu; Yaping Xu; Fahui Wang (Journal of Geographical Sciences, 2019)

Analyzing Population Density Disparity in China with GIS-automated Regionalization: The Hu Line Revisited - Fahui Wang; Cuiling Liu; Yaping Xu (Chinese Geographical Science, 2019)

Dietary Supplementation of Selenium-Enriched Probiotics Enhances Meat Quality of Broiler Chickens (Gallus gallus domesticus) Raised Under High Ambient Temperature - Alam Zeb Khan; Shahnawaz Kumbhar; Yunhuan Liu; Mohammad Hamid; Cuiling Pan; Sonia Agostinho Nido; Fahmida Parveen; Kehe Huang (Biological Trace Element Research, 2018)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Improving Production of Protease from Pseudoalteromonas sp. CSN423 by Random Mutagenesis - Cuiling Wu; Dan Liu; Xinghao Yang; Ribang Wu; Jiang Zhang; Jiafeng Huang; Hailun He (Marine Biotechnology, 2016)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Enhanced expression of the human CD14 protein in tobacco using a 22-kDa alpha-zein signal peptide - Xiuxia Liu; Li Sun; Cuiling Li; Aifang Yang; Juren Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Expression of TRPC homologs in endothelial cells and smooth muscle layers of human arteries - Ham Yip; Wing-Yee Chan; Pan-Cheung Leung; Hiu-Yee Kwan; Cuiling Liu; Yu Huang; Villaz Michel; David Tai-Wai Yew; Xiaoqiang Yao (Histochemistry and Cell Biology, 2004)